USE OF DOPAMINE ANTAGONISTS ON INDUCED SPAWNING OF INDIAN MAJOR CARPS - SINGH, KULDIP; DUTT, S.; ALI, M.; BISWAS, R. K. (Journal of Indian Fisheries Association, 2015)
To test the efficacy of the technique of using dopamine - antagonistswith pituitary extracts, experi~ents were conducted in July/August, 93,at the CIFE Fresh water Fish Farm, Powerkheda. In all, 35 sets (1 femalex 2 male in each set) were tried individually. 19 sets were treated withDomperidone (DOM) and Carp Pituitary Extract (CPE) and theyconstituted the experimental sets, while the rest 16 were treated withCPE and formed the control sets. The breeding, complete ovulation andhatching was 84.2%, 87.5% and 85.7%, respectively in the experimentalsets whereas it was 93. 7%, 60% and 72. 7%, respectively in case of controlsets. Experimental sets yielded 1.20 lakh spawn/kg body wt. (female) ascompared to 0.83 lakh spawn kg body wt. (female) received from controlsets on average basis. When DOM was used @ 50-60% there was 100%breeding success but when increased to 70%, breeding rate fell to 66%. Inmass breeding of Catla in the Circular hatchery DOM mixed with CPE in50:50 ratio gave excellent results.